Crossing intergroup borders. Forms of Social Brokerage in Italian Occupied Greece (1941-43) (History Journal «Jerónimo Zurita», 2022)
Adopting an approach informed by the sociology of power, this article investigates forms of intermediation between the Italian authorities and the local population in Axis-occupied Greece during the Second World War. As the Italians could not rely on large communities of “ethnic kin” in Greece – like e. g. the Germans in other European countries -, they had to largely resort to locals to govern the country both at government level and on a local scale. To conceptualize this form of intermediation, the paper first analyses sociological approaches to occupation and colonialism, outlining the main commonalities and differences between these two settings from the point of view of the sociology of power. It then proposes to understand the intermediation between occupiers and occupied with the sociological category of brokerage rather than the politically and morally charged term of collaboration. Using a wide array of sources - among others the records of the Italian military tribunals in Greece that prosecuted also Greek citizens -, the paper then explores everyday interactions with a micro-analytical approach, outlining main patterns of brokerage and its effects on the stratification of the Greek society.
Keywords: Second World War; Greece; Occupation; Social brokerage